Regulation of ppGpp Synthesis and Its Impact on Chloroplast Biogenesis during Early Leaf Development in Rice. (16th April 2022) - Ito, Kazuhiro; Ito, Doshun; Goto, Mina; Suzuki, Sae; Masuda, Shinji; Iba, Koh; Kusumi, Kensuke
Abstract: Guanosine tetraphosphate (ppGpp) is known as an alarmone that mediates bacterial stress responses. In plants, ppGpp is synthesized in chloroplasts from GTP and ATP and functions as a regulator of chloroplast gene expression to affect photosynthesis and plant growth. This observation indicates that ppGpp metabolism is closely related to chloroplast function, but the regulation of ppGpp and its role in chloroplast differentiation are not well understood. In rice, ppGpp directly inhibits plastidial guanylate kinase (GKpm), a key enzyme in GTP biosynthesis. GKpm is highly expressed during early leaf development in rice, and the GKpm-deficient mutant, virescent-2 ( v2 ), develops chloroplast-deficient chlorotic leaves under low-temperature conditions. To examine the relationship between GTP synthesis and ppGpp homeostasis, we generated transgenic rice plants over-expressing RSH3, a protein known to act as a ppGpp synthase. When RSH3 was overexpressed in v2, the leaf chlorosis was more severe. Although the RSH3 overexpression in the wild type caused no visible effects, pulse amplitude modulation fluorometer measurements indicated that photosynthetic rates were reduced in this line. This finding implies that the regulation of ppGpp synthesis in rice is involved in the maintenance of the GTP pool required to regulate plastid gene expression during early chloroplast biogenesis. We further investigated changes in the expressions of RelA/SpoT Homolog (RSH) genes encoding ppGpp synthases and hydrolases during the same period. Comparing the expression of these genes with the cellular ppGpp content suggests that the basal ppGpp level is determined by the antagonistic action of multiple RSH enzymatic activities during early leaf development in rice.